2019
DOI: 10.1177/2167702619873590
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Lagged Association Between Symptoms of Posttraumatic Stress Disorder and Perceived Centrality of a Terrorist Attack

Abstract: Numerous cross-sectional studies have found a positive association between level of event centrality and symptoms of posttraumatic stress disorder (PTSD), but the temporal course of this relationship is unclear. We aimed to investigate the concurrent and longitudinal association between event centrality and symptoms of PTSD in a trauma-exposed sample. In total, 319 survivors of the 2011 massacre on Utøya island, Norway, were interviewed 14 to 15 and 30 to 32 months after the event. A cross-lagged panel model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…These findings add to prior evidence that elevated event-centrality is concurrently and longitudinally associated with increased event-related psychopathology following loss-events (Boelen, 2012a(Boelen, , 2017 as well as other adverse events (Blix et al, 2016;Boals & Ruggero, 2015). We did not assess loss-centrality at a later point; intriguingly, a recent study indicated that, among people exposed to terror, PTS severity prospectively predicted later event-centrality but not vice versa (Glad et al, 2020). Whether elevated PG or other psychopathology after bereavement similarly predicts later loss-centrality, needs further scrutiny.…”
Section: Discussionsupporting
confidence: 55%
“…These findings add to prior evidence that elevated event-centrality is concurrently and longitudinally associated with increased event-related psychopathology following loss-events (Boelen, 2012a(Boelen, , 2017 as well as other adverse events (Blix et al, 2016;Boals & Ruggero, 2015). We did not assess loss-centrality at a later point; intriguingly, a recent study indicated that, among people exposed to terror, PTS severity prospectively predicted later event-centrality but not vice versa (Glad et al, 2020). Whether elevated PG or other psychopathology after bereavement similarly predicts later loss-centrality, needs further scrutiny.…”
Section: Discussionsupporting
confidence: 55%
“…There are several possible explanations for why we observed that PTSS predicted centrality in the present sample even though early literature suggests the opposite. One possibility raised by Glad et al (2020) is that different studies have examined the association between PTSD and event centrality during different timeframes, which can affect longitudinal findings. In addition, the current study was the first to examine this association longitudinally in the acute period following traumatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…During the massacre, the survivors experienced high levels of trauma exposure, including life threat, witnessing people being injured or killed, hearing people scream in pain and fear, the intense and persistent sound of gun shots, and the loss of someone close (Glad, Jensen, Hafstad, & Dyb, 2016 ). The survivors have reported high levels of peritraumatic reactions (Dyb et al, 2014 ), and high levels of event centrality (Glad, Czajkowski, Dyb, & Hafstad, 2019 ).…”
Section: Methodsmentioning
confidence: 99%